2017
DOI: 10.1088/1367-2630/aa91c8
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the dynamics of low temperature dielectric relaxation of ordinary perovskite ferroelectrics

Abstract: The temperature dependence of the dielectric response of ordinary ferroelectric materials exhibits a frequency-independent anomalous peak as a manifestation of the ferroelectric to paraelectric phase transition. A second anomaly in the permittivity has been reported in different ferroelectric perovskite-type systems at low temperatures, often at cryogenic temperatures. This anomaly manifests as a frequency-dependent local maximum, which exhibits similar characteristics to that observed in relaxor ferroelectric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…This methodology is helpful in systems where their dynamic relaxation achieve a SA pattern described by:as is the case of SCL and RF systems. MFR has been recently extended for studying the low-temperature dielectric relaxations of normal ferroelectrics 31 , but this approach has never applied before to study the dynamic of RF.…”
Section: Resultsmentioning
confidence: 99%
“…This methodology is helpful in systems where their dynamic relaxation achieve a SA pattern described by:as is the case of SCL and RF systems. MFR has been recently extended for studying the low-temperature dielectric relaxations of normal ferroelectrics 31 , but this approach has never applied before to study the dynamic of RF.…”
Section: Resultsmentioning
confidence: 99%
“…The parameters τ 0 and ∆E 0 define the relaxation time and activation energy at high temperatures, respectively, 𝑛𝑛 is a local order parameter and 𝑇𝑇 𝑁𝑁 is the divergence (freezing) temperature. 12,31,32 Noted that considering 𝑇𝑇 𝑟𝑟 = 𝑇𝑇 𝑔𝑔 and 𝑛𝑛 = 1 the classical equation of the VFT-fragility is reproduced. As shown in Eq.…”
Section: Fragility In Relaxor Ferroelectricsmentioning
confidence: 99%
“…This procedure was first successfully applied to a wide experimental data-set, ranging from low molecular weight liquids and polymers to liquid crystals and plastic crystals [26,27]. Furthermore, the procedure was recently applied to the study of the low-temperature di electric relaxations of ordinary ferroelectrics, and demonstrated the effectiveness of this approach for revealing changes in the dynamic behavior of these systems [28].…”
mentioning
confidence: 99%